Vaccination Is Associated With Shorter Time to Target Cycle Threshold Value in Patients With SARS-CoV-2 Omicron Variant - Wu, Jiajun; Wei, Yong; Shen, Feng; Zhu, Shun; Lu, Yingying; Tian, Xue; Zhang, Pengyu (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Limited data are available on the responses to vaccination for SARS-CoV-2 Omicron Variant in Chinese population. This study aimed to investigate whether vaccination could alter the disease course of SARS-CoV-2 Omicron Variant. Methods: It was a retrospective cohort which included 142 patients who had no or mild symptoms and were admitted to our department for centralized isolation after being locally infected with SARS-CoV-2 Omicron Variant from the 4th to the 30th March 2022 in Shanghai China. Results: Of the 142 subjects with the mean age of 43.1 years, 53.5% were male and 90.8% had been vaccinated before the infection. Comparing the vaccinated with the unvaccinated, there was no difference in patient characteristics, but patients with vaccination had shorter time to target cycle threshold value (TtCT) (Vaccinated vs Unvaccinated, 12.6±3.4 vs 14.8±4.7 days, P=0.039). There was no difference in TtCT between heterogeneous and homologous vaccination. Of subjects with homologous vaccination, 43.1% were vaccinated with CoronaVac (Sinovac Life Science), 47.2% with Sinopharm BBIBP-CorV, 4.9% with Sinopharm WIBP, 3.3% with CanSinoBio and 1.6% with Zhifei Longcom. No difference in TtCT was observed among different vaccines. Comparing two-dose primary vaccination with three-dose booster vaccination, we found no difference in TtCT either. Conclusion: Vaccination is associated with shorter TtCT in patients with SARS-CoV-2 Omicron Variant.